Pseudomonas aeruginosa pili and flagella mediate distinct binding and signaling events at the apical and basolateral surface of airway epithelium. - Iwona Bucior; Julia F Pielage; Joanne N Engel (PLoS Pathogens)
Pseudomonas aeruginosa, an important opportunistic pathogen of man, exploits numerous factors for initial attachment to the host, an event required to establish bacterial infection. In this paper, we rigorously explore the role of two major bacterial adhesins, type IV pili (Tfp) and flagella, in bacterial adherence to distinct host receptors at the apical (AP) and basolateral (BL) surfaces of polarized lung epithelial cells and induction of subsequent host signaling and pathogenic events. Using an isogenic mutant of P. aeruginosa that lacks flagella or utilizing beads coated with purified Tfp, we establish that Tfp are necessary and sufficient for maximal binding to host N-glycans at the AP surface of polarized epithelium. In contrast, experiments utilizing a P. aeruginosa isogenic mutant that lacks Tfp or using beads coated with purified flagella demonstrate that flagella are necessary and sufficient for maximal binding to heparan sulfate (HS) chains of heparan sulfate proteoglycans (HSPGs) at the BL surface of polarized epithelium. Using two different cell-free systems, we demonstrate that Tfp-coated beads show highest binding affinity to complex N-glycan chains coated onto plastic plates and preferentially aggregate with beads coated with N-glycans, but not with single sugars or HS. In contrast, flagella-coated beads bind to or aggregate preferentially with HS or HSPGs, but demonstrate little binding to N-glycans. We further show that Tfp-mediated binding to host N-glycans results in activation of phosphatidylinositol 3-kinase (PI3K)/Akt pathway and bacterial entry at the AP surface. At the BL surface, flagella-mediated binding to HS activates the epidermal growth factor receptor (EGFR), adaptor protein Shc, and PI3K/Akt, and induces bacterial entry. Remarkably, flagella-coated beads alone can activate EGFR and Shc. Together, this work provides new insights into the intricate interactions between P. aeruginosa and lung epithelium that may be potentially useful in the development of novel treatments for P. aeruginosa infections.